IMPROVEMENT OF MECHANICAL PROPERTIES OF STEEL WIRE BY THERMAL PROCESSING (British Journal of Global Ecology and Sustainable Development, 2022)
This article talks about increasing the mechanical properties of steel wires by thermal treatment, controlling the structure of thermal treatment steels, and the stages of thermal treatment.